Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/art.24060
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of prosthetic joint infection after total hip or knee replacement in patients with rheumatoid arthritis

Abstract: Objective Prosthetic joint infection is one of the most dreaded complications after total joint arthroplasty, a common procedure in patients with rheumatoid arthritis (RA). We conducted a study to evaluate potential risk factors of prosthetic joint infection and to clarify if RA is an independent predictor of this complication. Methods This study included all patients with RA who underwent total hip or knee replacement at the Mayo Clinic Rochester between January 1996 and June 2004. The association of potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
179
10
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(225 citation statements)
references
References 32 publications
14
179
10
16
Order By: Relevance
“…For THRs, the literature is conflicting (1,14,18). We did not confirm the findings of some study groups who reported an increased risk of deep infection in RA patients both in TKR and THR (13,16). Nor did we agree with Berbari et al (12), who reported no increased risk in TKR as well as THR (Table 3).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…For THRs, the literature is conflicting (1,14,18). We did not confirm the findings of some study groups who reported an increased risk of deep infection in RA patients both in TKR and THR (13,16). Nor did we agree with Berbari et al (12), who reported no increased risk in TKR as well as THR (Table 3).…”
Section: Discussioncontrasting
confidence: 82%
“…There are conflicting reports on whether this increased baseline risk of infections in RA patients might influence the risk of deep infection after primary total joint replacement surgery (1,5,(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The failure rate in our selected series is similar to previously published reports (Table 8) [26,29]. With regard to patients treated for infection, our failure rate of 25% is also comparable to the results of others (Table 8) [1,3]. Bongartz et al questioned whether this high rate of reinfection was actually due to persistent undetectable bacteria [3], whereas, Berbari et al demonstrated that a two-staged infection protocol may yield the best survival for patients with rheumatoid arthritis [1].…”
Section: Discussionsupporting
confidence: 91%
“…With regard to patients treated for infection, our failure rate of 25% is also comparable to the results of others (Table 8) [1,3]. Bongartz et al questioned whether this high rate of reinfection was actually due to persistent undetectable bacteria [3], whereas, Berbari et al demonstrated that a two-staged infection protocol may yield the best survival for patients with rheumatoid arthritis [1]. The high rate of failure observed in patients with rheumatoid arthritis is likely multifactorial as this autoimmune disease can directly affect a patient's bone quality [32], ligament integrity [22], and reactivation of joint synovitis can lead to further implant loosening [6].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to being a source of considerable morbidity, each infected arthroplasty is estimated to cost Ͼ$30,000, on average, to manage (16). Foremost among the potential explanations for this increased risk is that RA is a systemic autoimmune disorder, and it is managed with immunomodulatory drugs that have been linked to increased risk of infection (disease-modifying antirheumatic drugs, systemic corticosteroids, antimalarials, and biologic therapies) (54)(55)(56)(57). However, to our knowledge, the impact of biologic agents on the risk of infection following TJA has not been examined.…”
Section: Discussionmentioning
confidence: 99%